L-shaped association between ankle-brachial index and coronary heart disease in Chinese adults with hypertension - Wei Zhou; Yumeng Shi; Chao Yu; Tao Wang; Lingjuan Zhu; Huihui Bao; Xiaoshu Cheng (European Journal of Medical Research)
Abstract Background Prior research has established that an ankle-brachial index (ABI) ≤ 0.9 is positively correlated with cardiovascular events, including coronary heart disease (CHD). The present study aimed to elucidate the dose–response relationship between ABI and CHD within a hypertensive population. Methods We conducted a cross-sectional analysis involving 10,900 hypertensive patients, with CHD as the primary outcome. A generalized additive model (GAM) and fitted smoothing curve were employed to assess linearity and delineate the dose–response association between ABI and CHD. Results The cohort had a mean (SD) age of 68.3 (9.25) years, with 5129 (47.06%) being male. CHD was present in 552 (5.06%) participants. The fully adjusted odds ratio (OR) for CHD associated with ABI levels was 0.75 (95%CI 0.33–1.71). An L-shaped relationship between ABI and CHD was identified, with an inflection point at 1.07. Below this threshold, ABI showed a negative correlation with CHD (OR: 0.27; 95%CI 0.08–0.84), whereas above it, the association was not significant (OR: 3.08; 95%CI 0.60–15.80). Conclusions In Chinese adults with hypertension, ABI exhibits a nonlinear, L-shaped association with CHD, with the inflection point at 1.07.